Kebijakan Pembelajaran Tatap Muka Terbatas (PTMT) di Taman Kanak-Kanak Kuncup Kartika Kecamatan Jatinangor Kabupaten Sumedang - Ani Rindiani; Qiqi Yuliati Zaqiah (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
This study aims to find out how the Limited Face-to-face Learning (PTMT) policy is applied in Early Childhood Education institutions. This study uses kualitative methode and an analytical descriptive approach, methode of collecting data and information using observation, interviews and study documentation. Informants in this mini research are the Principal, Teachers and Parents. The research subjects were chosen with the consideration that TK Kuncup Kartika was the earliest educational institution to implement the PTMT policy in the Jatinangor District. The illustration is that the stages of making Limited Face-to-face Learning (PTMT) policies include regulatory studies, studies on the empirical condition of Covid 19 in the Jatinangor District, and observing parents' expectations. The implementation of the PTMT policy begins with carrying out pre-learning, then designing the Limited Face-to-Face Learning (PTMT) design during the Covid 19 Pandemic, and establishing Standard Operating Procedures (SOP) for learning in schools. The analysis of the results of the implementation of the Limited Face-to-Face Learning (PTMT) policy uses a SWOT analysis. The implementation of the Limited Face-to-Face Learning (PTMT) policy has a positive impact on schools, especially on increasing the achievement of six aspects of student development.